2021
DOI: 10.3352/jeehp.2021.18.11
|View full text |Cite
|
Sign up to set email alerts
|

Assessment methods and the validity and reliability of measurement tools in online objective structured clinical examinations: a systematic scoping review

Abstract: The coronavirus disease 2019 (COVID-19) pandemic has required educators to adapt the in-person objective structured clinical examination (OSCE) to online settings in order for it to remain a critical component of the multifaceted assessment of a student’s competency. This systematic scoping review aimed to summarise the assessment methods and validity and reliability of the measurement tools used in current online OSCE (hereafter, referred to as teleOSCE) approaches. A comprehensive literature review was under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…We think that an added positive educational impact of this experience is training students on using technology in learning and, later after graduation, in health care. This is supported by the findings of Felthun et al 16 in their systematic scoping review as they reported that teleOSCE could be able to equip the students with the requisite skills of practicing telemedicine in the future.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…We think that an added positive educational impact of this experience is training students on using technology in learning and, later after graduation, in health care. This is supported by the findings of Felthun et al 16 in their systematic scoping review as they reported that teleOSCE could be able to equip the students with the requisite skills of practicing telemedicine in the future.…”
Section: Discussionsupporting
confidence: 53%
“…Similar results were reported by Shaban et al, 13 who reported comparable Cronbach’s alpha values between online and conventional OSCE at their institution. Furthermore, Felthun et al 16 reported in their systematic scoping review that teleOSCE (online OSCE) could be able to improve the reproducibility of clinical assessments.…”
Section: Discussionmentioning
confidence: 99%
“…Recent efforts to deliver the teleOSCE and online OSCE orientation have been acceptable to students and examiners respectively [8,9]. A systematic review summarised the various attempts in the literature to incorporate an online element and discovered that while there is generally good validity and reliability, there is a need for systemic research to guide the ideal teleOSCE format [10].…”
Section: Background/rationalementioning
confidence: 99%
“…Recent efforts to deliver the tele-objective structured clinical examination (teleOSCE) and online OSCE orientation have been acceptable to students and examiners respectively [ 8 , 9 ]. A systematic review summarized the various attempts in the literature to incorporate an online element and discovered that while there is generally good validity and reliability, there is a need for systemic research to guide the ideal teleOSCE format [ 10 ]. As yet, no study has attempted to define and discuss the impact on the assessment outcome of separating students, patients, and assessors into different locations, and executing examinations online.…”
Section: Introductionmentioning
confidence: 99%
“…Online lectures in medical education have become prevalent with the advancement of technology and play important roles. [ 1 2 3 4 5 ] It offers students convenience and flexibility in terms of scheduling, circumstances, and transportation. [ 6 ] However, learning online is challenging.…”
Section: Introductionmentioning
confidence: 99%